Psychosocial Variables Associated with Immunosuppressive Medication Non-Adherence after Renal Transplantation - Scheel, Jennifer Felicia; Schieber, Katharina; Reber, Sandra; Stoessel, Lisa; Waldmann, Elisabeth; Jank, Sabine; Eckardt, Kai-Uwe; Grundmann, Franziska; Vitinius, Frank; de Zwaan, Martina; Bertram, Anna; Erim, Yesim (Frontiers in Psychiatry, 2018)
Introduction: Non-adherence to immunosuppressive medication is regarded as an important factor for graft rejection and loss after successful renal transplantation. Yet, results on prevalence and relationship with psychosocial parameters are heterogeneous. The main aim of the current study was to investigate the association of immunosuppressive medication non-adherence and psychosocial factors. Methods: In 330 adult renal transplant recipients (≥12 months post-transplantation), health-related quality of life, depression, anxiety, social support, and subjective medication experiences were assessed and their associations with patient-reported non-adherence was evaluated. Results: 33.6% of the patients admitted to be partially non-adherent. Non-adherence was associated with younger age, poorer social support, lower mental, but higher physical health-related quality of life. There was no association with depression and anxiety. However, high proportions of clinically relevant depression and anxiety symptoms were apparent in both adherent and non-adherent patients. Conclusions: In the post-transplant follow-up, kidney recipients with lower perceived social support, lower mental and higher physical health-related quality of life as well as younger age can be regarded as a risk group for immunosuppressive medication non-adherence. In follow-up contacts with kidney-transplant patients, physicians may pay attention to these factors. Furthermore, psychosocial interventions to optimize immunosuppressive medication adherence can be designed on the basis of this information, especially including subjectively perceived physical health-related quality of life and fostering social support seems to be of importance.